2023
DOI: 10.1186/s40634-023-00689-7
|View full text |Cite|
|
Sign up to set email alerts
|

Soft‐tissue tension during total hip arthroplasty measured in four patients and predicted using a musculoskeletal model

Masaru Higa,
Hiromasa Tanino,
Hiroshi Ito
et al.

Abstract: Purpose Soft-tissue tension around the hip joint is related to the incidence of dislocation after total hip arthroplasty (THA), but it remains difficult to quantify the soft-tissue tension during surgery. In this study, a three-dimensional force sensor-instrumented modular femoral head was developed and used to quantify soft-tissue tension during THA. The forces at the hip joint were also calculated using a three-dimensional musculoskeletal computer model to validate the measured forces. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Masaru Higa 1,2,3 , Hiromasa Tanino 1,2,3 , Hiroshi Ito 1,2,3 and Scott A. Banks 1,2,3 The correct version is shown in the authorgroup section above and the original article has been corrected.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Masaru Higa 1,2,3 , Hiromasa Tanino 1,2,3 , Hiroshi Ito 1,2,3 and Scott A. Banks 1,2,3 The correct version is shown in the authorgroup section above and the original article has been corrected.…”
mentioning
confidence: 99%
“…Correction: Soft-tissue tension during total hip arthroplasty measured in four patients and predicted using a musculoskeletal model Following publication of the original article [1], the author reported that the authors' affiliation assignment was incorrect. Masaru Higa 1,2,3 , Hiromasa Tanino 1,2,3 , Hiroshi Ito 1,2,3 and Scott A.…”
mentioning
confidence: 99%